The closing of the American mind - Bloom, Allan David 1930-1992 (Simon and Schuster Paperbacks, 2012)
In this book, the author (a distinguished political philosopher) argues that the social/political crisis of 20th-century America is really an intellectual crisis marked by obvious declines in appreciation of humanities, a drop in the qualitative output of our university systems, and a disquieting disconnect between today's students and the spiritual and cultural traditions of their heritage